Effectiveness of Customary Law Hita La Uwa Uwato as A Form of Settlement of Pidana Theft in The Country of Iha Seram District of West - Mohammad Sarfan Basyir Putuhena (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This paper explains about how the process of solving the crime of theft using the customary law of Hita La Uwa Uwato (Whip Law) of Iha State of Western Seram Regency, research methods is empirical research by a sociological juridical research approach, data collection instruments are carried out by interviews of predetermined respondents, review of legal documents and observations. The collected data is then analyzed qualitatively. This research shows that, the completion of the Crime of Theft by using customary law in the State of Iha District of Western Seram Maluku Province is very effective where the process is whipped using rattan in addition there are also additional sanctions given, namely indemnifying, as well as apologizing to the community, and the factors that affect its effectiveness are, the Legal factor, Law Enforcement, and Cultural and Community factors.